Caribbean Report 09-02-1990 - Fraser, Sonia (anchor); Crosskill, Hugh (correspondent); Ricardo, Joaquin (interviewee); Thomas, Clive (interviewee); Binnendijk, Chandra van (correspondent); O'Toole, Pamela (correspondent); Martin-Jenkins, Christopher (correspondent); Elcock, Ricardo (interviewee) (The British Broadcasting Corporation, 1990)
The program reports on the decision by the Dominican Republic to abandon their plans to export bananas to Europe, the result of opposition from the Caricom countries. Following the Financial Market news, the economic future of Suriname is of concern to Surinamese politicians in their quest to attract foreign investments. The next segment covers the clash between Cuba and the United States in the UN Security Council, with each accusing the other of violating international laws and conventions over a recent attack on a Cuban freighter by the US Coast Guard in the Gulf of Mexico. In the sporting segment, English cricketer Ricardo Elcock prepares to return to England due to a back injury. The report concludes with the stories of Caribbean interest appearing in the British press, including the visit of Rev. Jessie Jackson to London and racism in Russia.
1. Headlines (00:00-01:33)
2. Dominican Republic bows to Caricom pressure by pledging to abandon banana exports to Europe. Hugh Crosskill interviews Joaquin Ricardo, Secretary of State for Foriegn Affairs in Dominican Republic (01:34-06:03)
3. Financial News with comments from Clive Thomas, Professor of Economics at the University of Guyana (06:04-07:40)
4. Suriname seeks economic assistance. Chandra van Binnendijk reports from Paramaribo (07:41-10:00)
Keywords: Banana trade -- Dominican Republic.; Banana trade -- Caribbean Area.; Economic assistance -- Suriname.; Cuba -- Foreign relations -- 1990-; United States -- Foreign relations -- 1990-; Cricket -- Tournaments -- England.; Cricket -- Tournaments -- Caribbean Area.; Cricket players -- England.; Suriname -- Economic conditions.; Cuban American relations.